Impact of initial treatment and prognostic factors on postprogression survival in BRAF-mutated metastatic melanoma treated with dacarbazine or vemurafenib ± cobimetinib: a pooled analysis of four clinical trials - Paolo A. Ascierto; Antoni Ribas; James Larkin; Grant A. McArthur; Karl D. Lewis; Axel Hauschild; Keith T. Flaherty; Edward McKenna; Qian Zhu; Yong Mun; Brigitte Dréno (Journal of Translational Medicine, 2020)
Abstract Background We sought to identify patient subgroups with distinct postprogression overall survival (ppOS) outcomes and investigate the impact of original treatment assignment and initial postprogression treatment (ppRx) on ppOS. Methods Recursive partitioning analysis (RPA) was performed to model relationships between prespecified covariates and ppOS in patients with BRAF V600-mutated metastatic melanoma who had experienced progressive disease (PD) following treatment with cobimetinib plus vemurafenib, vemurafenib monotherapy, or dacarbazine in the BRIM-2, BRIM-3, BRIM-7, and coBRIM studies. Prognostic subgroups identified by RPA were then applied to pooled treatment cohorts. The primary endpoint was ppOS, defined as time from first PD to death from any cause. Results RPA identified baseline lactate dehydrogenase (LDH), baseline disease stage, Eastern Cooperative Oncology Group performance status at PD, and ppRx as significant prognostic factors for ppOS. Median ppOS was longest in patients with normal baseline LDH, stage M1c disease at baseline, and ppRx with immunotherapy or targeted therapy (12.2 months; 95% CI 10.3–16.1) and shortest in those with elevated baseline LDH > 2 × upper limit of normal (2.3 months; 95% CI 1.8–2.7). Original treatment assignment did not impact ppOS. Across treatment cohorts, patients treated with immunotherapy or targeted therapy after PD had better ppOS than those given other treatments. Conclusion A combination of factors at baseline (LDH, disease stage) and PD (performance status, ppRx) impact ppOS outcomes. ppRx with immunotherapy or targeted therapy is an independent prognostic factor for improved overall survival following progression regardless of original treatment. Trial registration The trials included in this analysis are registered with ClinicalTrials.gov: NCT00949702 (BRIM-2), NCT01006980 (BRIM-3), NCT01271803 (BRIM-7), and NCT01689519 (coBRIM).